Climate change mitigation and development: A study of selected ASEAN members / Anwar Hossain Chowdhury - Anwar Hossain , Chowdhury (2019)
Climate Change is a human induced global common problem, which require collective action. While the focus should be global, members of the Association of Southeast Asian Nation (ASEAN) should act collectively to address it. Consequently, this thesis seeks to evaluate the alternative proposals put forth to assess the impact of Climate Change on ASEAN members as a whole, and three bordering nations by deploying a Computable General Equilibrium (CGE) regional model, viz., the ASEAN Regional Integrated model of Climate and the Economy (ASEAN-RICE). Hence, the first objective of this thesis is to formulate a non-linear CGE “ASEAN-RICE” model to assess climate mitigation impact from the Intended Nationally Determined Contribution (INDC) submitted to the United Nations Framework Convention for Climate Change (UNFCCC) for ASEAN and for Malaysia over 100 years following the Paris Accord of 2015. The second objective is to analyse climate mitigation impact on the Association of Southeast Asian Nations (ASEAN) using the INDCs of these nations submitted to UNFCCC but over 50 years following the Marrakesh Proclamation of 2016. The third objective is to construct a low carbon economy index for Indonesia, Malaysia and Thailand. Dynamic non-linear CGE modelling and the 2010 input-output tables were deployed to estimate climate mitigation consequences under the INDC scenario and the business as usual (BAU) scenario (if existing practices are continued). In the Malaysian case an additional national plan scenario was included. The period 2010-2100 was selected for the first objective and 2010-2060 was selected for the second and third objectives. The results show that climate damage over the period 2010-2100 will fall from 2,722mtoe under the BAU scenario to 1,203mtoe under the national plan scenario and 699mtoe under the INDC scenario. Carbon concentration will fall from 11,912ppm under the BAU scenario to 9,714ppm under the national plan scenario and 8,592ppm under the INDC scenario. Since the abatement costs of the latter two are almost the same, the UNFCCC’s INDC scenario is the best option. In the ASEAN as a whole case, the results indicate that atmospheric concentration of carbon and temperatures under the INDCs scenario will fall from 390ppm and 0.80°C respectively in 2010 to 298 ppm and 0.71°C respectively in 2060. Under the BAU scenario it will fall from 390ppm and 0.80°C respectively in 2010 to 351ppm and 0.79°C respectively in 2060. Cumulative climate damage under BAU and optimal scenarios will rise from MYR8billion for both in 2010 to MYR579Billion and MYR513Billion in 2060. The reduction in carbon emissions under the optimal scenario can be achieved without compromising GDP growth. The low carbon economy index estimations for Indonesia, Malaysian and Thailand suggest that Indonesia will have to introduce aggressive Climate Change mitigation strategies to catch up with Malaysia. Thailand appears to keep up the pace with Malaysia. Overall, this thesis produced results that show that the introduction and strict application of INDCs will help mitigate Climate Change and global warming among ASEAN economies in general, and Malaysia in particular.